2021
DOI: 10.2147/nss.s315375
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in Studies on the Role of Neuroendocrine Disorders in Obstructive Sleep Apnea–Hypopnea Syndrome-Related Atherosclerosis

Abstract: Cardiovascular disease is a common cause of death worldwide, and atherosclerosis (AS) and obstructive sleep apnea-hypopnea syndrome (OSAHS) critically contribute to the initiation and progression of cardiovascular diseases. OSAHS promotes endothelial injury, vascular smooth muscle cell (VSMC) proliferation, abnormal lipid metabolism, and elevated arterial blood pressure. However, the exact OSAHS mechanism that causes AS remains unclear. The nervous system is widely distributed in the central and peripheral reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 166 publications
(195 reference statements)
0
3
0
Order By: Relevance
“…MMSE is widely used in the screening of cognitive dysfunction due to its strong sensitivity, easy operation, and less time-consuming. However, MMSE is relatively simple and easy to miss diagnosis of mild cognitive impairment [ 7 ]. ESD is a scale commonly used to assess brain cognitive function at home and abroad in recent years.…”
Section: Literature Reviewmentioning
confidence: 99%
“…MMSE is widely used in the screening of cognitive dysfunction due to its strong sensitivity, easy operation, and less time-consuming. However, MMSE is relatively simple and easy to miss diagnosis of mild cognitive impairment [ 7 ]. ESD is a scale commonly used to assess brain cognitive function at home and abroad in recent years.…”
Section: Literature Reviewmentioning
confidence: 99%
“…NPY exerts its biological effects by binding to receptors, specifically the inflammation related NPY-Y1, NPY-Y2, and NPY-Y5 receptors [ 26 ]. The high distribution of these receptors in the hypothalamic tissue suggests that exploring the correlation between NPY levels in the brain, peripheral inflammatory response, and CAS may be a valuable approach.…”
Section: Discussionmentioning
confidence: 99%
“…We found that the indoxyl sulfate level was higher in patients with OSA than in the controls. The repetitive episodes of apnea/ hypopnea in OSA patients increase the level of glucocorticoids and inflammatory cytokines, resulting in increased oxidative stress (Stanek, Brożyna-Tkaczyk, and Myśliński, 2021;Wang et al, 2021). Consequently, oxidative stress and redox imbalance lead to an accumulation of reactive oxygen species (ROS).…”
Section: Discussionmentioning
confidence: 99%